Development and Evaluation of a Nanosponge-Based Gel for Combined Hydrocortisone and Benzocaine Delivery in Psoriasis (International Journal of Food and Nutritional Sciences, 2022)
The study aimed to develop a topical gel based on nanosponges (NS) containing a combination of benzocaine and hydrocortisone for psoriasis treatment. This project aimed to formulate topical nanosponges-based gel that includes a combination of hydrocortisone and benzocaine that can potentially be utilized for the treatment of psoriasis. The drug-loaded nanosponges were formulated using ethyl cellulose and polyvinyl alcohol as polymer and copolymer, with dichloromethane as an organic solvent. A fully randomized factorial design(32) examined 9 potential experimental runs. Formulation F1 was achieved after optimization, with a 195.1 nm particle size, 80.64% entrapment efficiency, 96.53% in-vitro release, 17.2 mV zeta potential, 81.69% drug loading, 50.6% percentage yield, 122% percent swelling. The gel was formulated by adjusting the concentration of polymer Guar gum and gelling agent Carbopol-934. A group of animals was used in ex vivo permeation and skin irritation study to check the safety & efficacy of the formulation. Hydrocortisone combined with benzocaine ismore effective against psoriasis and inflammation than Hydrocortisone alone. The nanogel showed drug release through 12 hours, indicating that the combination of Benzocaine and hydrocortisone significantly increased anti-psoriatic efficacy. Therefore, the suggested Nanosponges-based hydrogel will be a more effective drug delivery method for anti-psoriatic therapy.